Intravenous lidocaine infusion in a case of severe COVID-19 infection - Anna Rylova; Seema Chowdhury; Houman Amirfarzan; Kay B Leissner; Roman Schumann (Wolters Kluwer Medknow Publications, 2021)
A subset of patients with COVID-19 develops a severe inflammatory response that may lead to respiratory and multiorgan failure. Effective treatment strategies to mitigate or interrupt this self-destructive inflammatory process are limited. The local anesthetic lidocaine has anti-inflammatory properties in addition to its analgesic, antiarrhythmic, and sedating effects that may be beneficial in critically ill COVID-19 patients. We report the case of a patient with COVID-19 induced severe respiratory distress who was intubated and received supportive treatment including proning and neuromuscular blockade. He developed a strong inflammatory response that we treated with an intermittent lidocaine infusion resulting in subsequent resolution. This case occurred prior to emerging data from a large dexamethasone use trial that demonstrated a survival benefit from its use in hospitalized COVID-19 patients. At the time, lidocaine was the only anti-inflammatory medication our patient received.